Analytical and Numerical Study on the Performance of ‎Supersonic Ejector at Different Operating Conditions ‎and Working Fluids - S. K. Yadav (Isfahan University of Technology, 2021)
The computation of ejector geometry for a given fluid is essential and plays a crucial role in creating an ejector profile and performance analysis. The current paper discusses the constant rate of momentum change (CRMC) approach using a real gas equation for ejector design. The numerical analysis is carried to validate the analytical geometry and the effect of operating parameters on the entrainment ratio. The variation in entrainment ratio for the different working fluids has also been studied on the geometry computed for water-vapour. It is observed that the entrainment ratio of the ejector significantly varies with the change in operating conditions and working fluids. The numerically predicted entrainment ratio is ~0.354 compared to the on-design entrainment ratio 0.4 for water vapor, while the predicted entrainment ratio for other working fluids is ~0.319, ~0.314, and ~0.36 for air, N2, and CO2, respectively‎.